2016
DOI: 10.5120/ijca2016910789
|View full text |Cite
|
Sign up to set email alerts
|

Particle Swarm Optimization based Feature Selection

Abstract: Feature Selection is a pre-processing step in knowledge discovery from data (KDD) which aims at retrieving relevant data from the database beforehand. It imparts quality to the results of data mining tasks by selecting optimal feature set from larger set of features. Various feature selection techniques have been proposed in past which, unfortunately, suffer from unavoidable problems such as high computational cost and getting stuck into the local optima. Evolutionary algorithms such as Particle Swarm Optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…(a) Randomly initializing velocity and particle population; (b) Starting new iteration; (c) Evaluating the fitness function for all particles; (d) Determining p-best of each particle and replacing the p-best when it is better than the previous one; (e) Determining g-best value; (f ) Updating each particle velocity by Eq. (15).…”
Section: Feature Selection By Particle Swarm Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Randomly initializing velocity and particle population; (b) Starting new iteration; (c) Evaluating the fitness function for all particles; (d) Determining p-best of each particle and replacing the p-best when it is better than the previous one; (e) Determining g-best value; (f ) Updating each particle velocity by Eq. (15).…”
Section: Feature Selection By Particle Swarm Optimizationmentioning
confidence: 99%
“…To aid the feature selection process and determining hidden node number, PSO is chosen as algorithm in this work. Previous study has shown a promising result in using PSO for selecting features [15]. PSO showed minor accuracy reduction with significantly faster performance compared to other algorithms such as GA [16].…”
mentioning
confidence: 93%